Efektifitas Terapi Akupunktur Menggunakan Kombinasi Titik Zusanli (ST36), Titik Sanyinjiao (SP6), Titik Yanglingquan (GB34) Dan Titik Taixi (KI3) Untuk Penurunan Nyeri Pada Osteoarthritis Di Griya Sehat Prima Hati Surakarta - Maria Dewi Christiyawati (Jurnal Keterapian Fisik, 2017)
Abstract : Osteoarthritis, The Point Of Sanyinjiao (SP6), The Point Of Taixi (KI3), Yanglingquan (GB34), And Point Zusanli (ST36). Osteoarthritis (OA) is a degenerative disorder that is on the mark with loss of cartilage. Based on the preliminary studies have been conducted on the elderly in Griya Sehat Prima Hati Surakarta, 18 elderly pleased given acupuncture therapy. Acupuncture therapy on a case of Osteoarthritis can improve blood circulation, improve the cartilage matrix, reducing the narrowing of joint bones and eliminate pain in knee Osteoarthritis cases. The purpose of this research is to know is there anyThe Influence Of Acupuncture Therapy Using A Combination Of Point Zusanli (ST36), Point Sanyinjiao (SP6), Yanglingquan Point (GB34), And The Point Of Taixi (KI3) to decrese pain in cases of Osteoarthritis elderly in the village of Kiringan and Umbulsari Klaten Polanharjo Ponggok. The research conducted during the month of September 2016 until June 2017 in Griya Sehat Prima Hati Surakarta with make pricking uses a Combination of Point Zusanli (ST36), the point of Sanyinjiao (SP6), Yanglingquan Point (GB34), and the point of Taixi (KI3). The therapy performed during 12 times therapy. This type of research this is a Pretest-Posttest Experimental pre that use design research One Group Pretest – Posttest Design. The data analyzed using paired t-test with significant degrees of 0.05. Measurement of pain sensations using a Numeric Rating Scale (NRS) (patient own set skore pain pain range). Statistical Tests by using the test of Paired t- test values available by sifgnifikan p = 0.000, if ρ ˂ 0.05 then Ho was rejected and Ha be accepted meaning therapy acupuncture Zusanli (ST36) point, the point of Sanyinjiao(SP6), Yanglingquan point (GB34), and the point of Taixi (KI3) have benefits to reduce pain in cases of Osteoarthritis (OA).